Defective Carbon–CoP Nanoparticles Hybrids with Interfacial Charges Polarization for Efficient Bifunctional Oxygen Electrocatalysis. Issue 18 (21st February 2018) - Lin, Yunxiang; Yang, Li; Zhang, Youkui; Jiang, Hongliang; Xiao, Zijian; Wu, Chuanqiang; Zhang, Guobin; Jiang, Jun; Song, Li
Abstract: The development of efficient catalysts for both oxygen reduction and evolution reactions (oxygen reduction reaction (ORR) and oxygen evolution reaction (OER)) is central to regenerative fuel cells and rechargeable metal–air batteries. It is highly desirable to achieve the efficient integration of dual active components into the catalysts and to understand the interaction between the dual components. Here, a facile approach is demonstrated to construct defective carbon–CoP nanoparticle hybrids as bifunctional oxygen electrocatalysts, and further probe the interfacial charge distribution behavior. By combining multiple synchrotron‐based X‐ray spectroscopic characterizations with density functional theory calculations, the interfacial charge polarization with the electrons gathering at the defective carbon surface and the holes gathering at the CoP surface due to strong interfacial coupling is revealed, which simultaneously facilitates the ORR and OER with remarkable bifunctional oxygen electrode activities. This work not only offers a bifunctional oxygen catalyst with outstanding performance, but also unravels the promoting factor of the hybrids from the view of interfacial charge distribution. Abstract : The charge redistribution in the CoP and defective carbon interface leads to the electrons gathering at the defective carbon surface and the holes gathering at the CoP surface, which simultaneously facilitates the oxygen reduction reaction and oxygen evolution reaction with a specific bifunctional oxygen electrode activity of 0.76 V.